Pengaturan Mekanisme Gugatan Derivatif Oleh Pemegang Saham Sebagai Upaya Perlindungan Perseroan Terbatas Terhadap Perbuatan Direksi Yang Merugikan - Yusro, Mochammad Abizar; Sihabudin; Kusumadewi, Amelia Sri (Faculty of Law, Universitas Brawijaya, 2022)
This research studies the issue regarding the urging regulation of the mechanism of derivative action performed by a shareholder as a measure to protect a limited liability company from any disadvantaging conduct done by the company director, which is only governed in one article in Law Number 40 of 2007 concerning Limited Liability Company, and there is no specific regulation concerning trial procedures at court. The legal issue regarding the norm incompleteness serves as the basis of this study. This study employed normative law research, statutory, and conceptual approaches. Primary secondary, and tertiary legal materials were analyzed using descriptive analyses, grammatical, systematic, and teleological interpretations. These interpretation techniques aim to identify and determine the content and the meaning of the legal provision regarding the regulation of the derivative action mechanism by a shareholder to protect the company from the advantaging director. This study delved into the answer to this problem through several perspectives such as philosophical, juridical, sociological, economic, and historical perspectives. This study also delved into the logical fallacy commonly happening in earlier studies on derivative action and elaborates on the liability of the director regarding his/her disadvantaging action, while the director is given the fiduciary duty to take care of the company. This liability is also seen from fiduciary parameters such as the duty of good faith, the duty of loyalty, and the duty of care andseveral corporate doctrines such as piercing of the corporate veil, ultra vires, and self-dealing. The derivative action as the liability held by the director is believed to facilitate recovery and provide compensation for the company.